Biochemical characterization of the human ubiquitous glucose‐6‐phosphatase in neutrophil granulocytes - Zsigmond Lédeczi; Klaudia Németh; Tamás Kardon (FEBS Open Bio)
Glucose‐6‐phosphatase‐β (G6PC3) is a ubiquitous phosphatase present in the endoplasmic reticulum, which, unlike G6PC1, is not responsible for maintaining blood glucose level under starvation. Recently, G6PC3 has been shown to play an important role in neutrophil granulocytes, eliminating the toxic metabolite 1,5‐anhydroglucitol‐6‐phosphate. The present study aimed to look for alternative substrates for the enzyme and outline the expression changes in the parts of this multicomponent system during neutrophil granulocyte differentiation. We determined the kinetic characteristics of recombinant human G6PC3 towards different sugar phosphates, and the transport of these compounds was also measured in rat liver microsomes. We found that all investigated sugar phosphates are substrates for G6PC3, although their microsomal transport is much slower than that of glucose‐6‐phosphate. Using the HL‐60 promyelocytic leukemia cell line as an in vitro model system for myeloid differentiation, we found no significant differences in enzyme expression and phosphatase activity latency between undifferentiated and differentiated cells. Our results provide novel insights into the possible role of G6PC3 in the dephosphorylation of alternative sugar phosphates or their metabolites synthesized in the endoplasmic reticulum and confirm the potential feature of the enzyme in the promyelocytic stage as well. These findings contribute to our knowledge of intracellular carbohydrate metabolism of neutrophil granulocytes, which facilitates further research directions to better understand the underlying mechanisms of neutropenias.